STUDI TEKNO-EKONOMI PROSES PIROMETALURGI DAUR ULANG BATERAI LITHIUM MANGANESE OXIDE (LMO) DAN LITHIUM IRON PHOSPHATE (LFP) - Rininta Triaswinanti; Rahmadhani Triastomo; Angella Natalia Ghea Puspita; Abdul Hapid (J@ti Undip: Jurnal Teknik Industri, 2023)
Limbah baterai lithium-ion diproyeksikan akan meningkat seiring dengan peningkatan jumlah kendaraan listrik. Teknologi daur ulang baterai menjadi perhatian penting terutama dalam mendukung percepatan program Kendaraan Bermotor Listrik Berbasis Baterai (KBLBB). Penelitian ini berfokus pada studi tekno-ekonomi pembangunan pilot plant daur ulang baterai Lithium Manganese Oxide (LMO) dan Lithium Iron Phosphate (LFP) secara pirometalurgi. Kapasitas input daur ulang baterai LFP dan LMO adalah 8.000 ton/tahun.  Nilai Internal Rate of Return (IRR), Net Present Value (NPV), Payback Period (PBP), dan Profitability Index (PI) daur ulang baterai LMO berturut-turut adalah 12,57%, Rp 7.583.346.464,-, 5,85 tahun, dan 2,39. Sedangkan untuk daur ulang baterai LFP berturut-turut adalah 11,15%,  -Rp 11.235.266.123,-, 6,23 tahun, dan 2,32. Hal ini mengindikasikan daur ulang baterai LMO lebih menjanjikan dibandingkan daur ulang baterai LFP. Dari segi analisis sensitivitas, diketahui bahwa daur ulang baterai LMO dan LFP ini lebih sensitif terhadap perubahan harga produk dibandingkan dengan perubahan harga reagen dan nilai OPEX. Emisi gas CO2, pada proses daur ulang baterai LMO lebih sedikit daripada baterai LFP, sehingga pencemaran lingkungan yang dihasilkan lebih minim. Untuk meminimalisir emisi gas ini, dapat dilakukan instalasi peralatan wet scrubber dan implementasi sistem Carbon Capture and Storage (CCS)/Carbon Capture, Utilization, and Storage (CCUS). Abstract[Techno-Economic Study of Pyrometallurgy Process of Lithium Manganese Oxide (LMO) and Lithium Iron Phosphate (LFP) Battery Recycling] Lithium-ion battery waste is projected to increase along with electric vehicle growth. Battery recycling technology is an important concern, especially in supporting the acceleration of the Battery-Based Electric Vehicle program. This research focuses on the techno-economic study of the construction of a Lithium Manganese Oxide (LMO) and Lithium Iron Phosphate (LFP) battery recycling pilot plant using the pyrometallurgy method to produce an input capacity of LFP and LMO battery recycling of 8,000 tons/year. The Internal Rate of Return (IRR), Net Present Value (NPV), Payback Period (PBP), and Profitability Index (PI) of the LMO battery recycling are 12,57%, Rp 7.583.346.464,-, 5,85 years, and 2,39 respectively. Meanwhile, for LFP battery recycling, the values are 11,15%, -Rp 11.235.266.123,-, 6,23 years, and 2,32 respectively. These values indicate that LMO battery recycling is more promising than LFP battery recycling. In terms of sensitivity analysis, it is known that LMO and LFP battery recycling are more sensitive to changes in product prices than changes in reagent prices and OPEX values. CO2 emissions in the LMO battery recycling process are lower than those from LFP batteries, resulting in more minimal environmental pollution. To minimize these gas emissions, the installation of wet scrubber equipment and the implementation of Carbon Capture and Storage (CCS)/Carbon Capture, Utilization, and Storage (CCUS) can be done.Keywords: Lithium Ion Battery; Techno-Economy; Battery Recycling; NPV; IRR; PBP; PI; Sensitivity Analysis; Pyrometallurgy